IN- VITRO CULTURE OF ARTEMISIA AUCHERI BOISS. ON FOUR DIFFERENT TISSUE CULTURE MEDIA FOR COMPARATIVE CYTOTOXIC EFFRCTS AND GROWTH - Gharehmatrossian, Sormeh; Popov, Yu; Ghorbanli, Mahlagha; Safaeian, Shila (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Artemisia genus is an important medicinal plant in Iran. The effect of four different culture media was investigated on growth and cytotoxic production of Artemisia aucheri in callus culture after 20th subculture. Methods: Callus induction was initiated from seedling on a Murashige and Skoog (MS) basal medium containing different concentrations of vitamins and combinations of growth regulators. Cytotoxicity of methanolic extract of callus culture grown on different culture media was assessed using the brine shrimp assay. Result: Different concentrations and combinations of phytohormones had no significant influence on callus fresh weight, callus dry weight and percentage of callus dry matter. However, cytotoxic production seems depend on the lowest level of growth index (1.94 ± 0.12) because from among the four methanolic extracts of the four isolated cultures of A. aucheri tested on MS medium supplemented with high level of 6-benzylaminopurine (BAP), naphthalene acetic acid (NAA) and thiamine-HCl was found to have the cytotoxicity (LC50 < 1000µg/ml) using brine shrimp lethality assay. Methanolic extracts of callus culture on MS medium containing kinetin (Kin), indole-3-acetic (IAA) and 2,4-dichlorophenoxy acetic acid (2,4,D) had the highest level of growth index (4.31 ± 0.56) and no cytotoxic effect was observed. Conclusion: In the establishment of cell culture, high level of BAP, NAA and thiamine-HCl were the best plant growth regulators in supporting the cytotoxic production. This is the first report on the use of phytohormones on the establishment of cell cultures in cytotoxic production of A. aucheri. KEYWORDS: Artemisia aucheri, Artemia franciscana, cytotoxic, tissue culture, methanol extract, growth index